2019
DOI: 10.1063/1.5125919
|View full text |Cite
|
Sign up to set email alerts
|

Polaronic nature of a muonium-related paramagnetic center in SrTiO3

Abstract: The hyperfine features and thermal stability of a muonium (Mu)-related paramagnetic center were investigated in the SrTiO 3 perovskite titanate via muon spin rotation spectroscopy. The hyperfine coupling tensor of the paramagnetic center was found to have prominent dipolar characteristics, indicating that the electron spin density is dominantly distributed on a Ti site to form a small polaron near an ionized Mu + donor. Based on a hydrogen-Mu analogy, interstitial hydrogen is also expected to form such a polar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Moreover, the emergence of the second Mu 0 states with a greater A d below ∼5 K coexisting with the diamagnetic state [53] recalls the situation in ZnO. Recent studies on Mu in SrTiO 3 have also reported electronic states similar to TiO 2 [55], where the localized moment at the Ti site is as large as ∼0.33µ B , suggesting a more strongly localized state (small polaron-like) than that in TiO 2 .…”
Section: Mu In Insulating/semiconducting Oxidessupporting
confidence: 56%
See 1 more Smart Citation
“…Moreover, the emergence of the second Mu 0 states with a greater A d below ∼5 K coexisting with the diamagnetic state [53] recalls the situation in ZnO. Recent studies on Mu in SrTiO 3 have also reported electronic states similar to TiO 2 [55], where the localized moment at the Ti site is as large as ∼0.33µ B , suggesting a more strongly localized state (small polaron-like) than that in TiO 2 .…”
Section: Mu In Insulating/semiconducting Oxidessupporting
confidence: 56%
“…Thus, considering that the local atomic configuration of Mu/H is almost identical between ZnO and IGZO [58], the strong electron-phonon coupling is another important factor to enhance the localization of electrons around the OMu − complex. This invokes the precaution that the activation energy for the promotion from Mu 0 D to Mu + D cannot be simply attributed to ε + ; it includes the contribution of the adiabatic potential barrier for the electron between the localized state and the continuous state [55]. The effect of the electron-phonon coupling has also been theoretically investigated in terms of the duality of the conduction band carriers in TiO 2 and SrTiO 3 , which can be in both the continuous state and the deep level (self-trapped) state in the gap [95].…”
Section: Polaron States Mimicking Donor-like Mumentioning
confidence: 99%
“…Thus, we are confident in assigning S 1 to C + . This assignment directly implies that the f 2 → f 1 transition around 225 K corresponds to a charge-state transition from neutral to positive, which we characterize as a complex dissociation [30], i.e. a separation of the polaron and the oxygen-bound muon, rather than an ionization of the bound electron to the conduction band.…”
mentioning
confidence: 89%
“…Since isolated H is extremely hard to study directly, most information about its dopant characteristics comes from the study of muonium (Mu=[µ + e − ]), a light H analog with virtually identical electronic structure, which is experimentally accessible via the muon-spin-rotation (µSR) technique [24][25][26][27]. Recent µSR studies reported polaronic Mu centers in non-magnetic TMOs such as SrTiO 3 and TiO 2 [28][29][30], in which an oxygen-bound, positive muon and a small polaron located on a neighboring TM ion form an overall charge-neutral complex, suggesting that isolated H defects form analogous H-polaron centers. Recently, muon-polaron complexes have been shown to exist in the antiferromagnet Cr 2 O 3 [31].…”
mentioning
confidence: 99%
“…Such configurations have been observed recently in experiments on TiO 2 and SrTiO 3 . [17][18][19] The well-defined hyperfine lines of these states indicate that the muon -electron (polaron) complex is formed promptly (in the ns time range) after implantation. The muon -polaron concept was also applied in Ref.…”
mentioning
confidence: 98%